Rechtsentwicklungen in Deutschland - Laufs, Adolf (De Gruyter Recht, 2011)
Biographical note: Adolf Laufs, Universität Heidelberg.
Includes bibliographical references and index
Keywords: Lehrbuch; Geschichte; Recht; Deutschland